Endangered Future Of Street Children: A Study Of Their Psychosocial Condition (Journal of Namibian Studies : History Politics Culture, 2023)
This paper is focusing on the street children’s mental health, social relationships, coping mechanisms, and access to essential services. Street children, who face the challenges of homelessness, family estrangement, and poverty, often endure compounded psychosocial difficulties like depression and sometimes violent and hyperaggressive behaviour, due to insecurity related to limited access to social support, healthcare, and educational opportunities. The research aims to understand this vulnerable population's unique challenges and survival strategies, providing insights that may inform future social work interventions and policies.This study investigates the psychosocial conditions of street children in the Lucknow district of Uttar Pradesh, India by using a mixed-methods approach, the study involved 100 street children aged 6–17. Data collection included structured interviews, surveys, and field observations. Qualitative insights were gained through semi-structured interviews, capturing the children's experiences, emotional states, and relationships. Quantitative data were gathered through surveys to measure key psychosocial indicators, such as the prevalence of anxiety, depression, substance use, and peer support networks. Field observations provided context to understand the daily realities and environmental challenges street children face in urban settings.The study concludes that the psychosocial conditions of street children in Lucknow are complex and multi-faceted, with critical needs mental health, social support, and access to fundamental resources. It emphasizes the necessity for a comprehensive, multi-sectoral approach involving Government agencies, Non-Government Organizations, and community-based services to address these challenges. Such interventions should prioritize mental health services, education accessibility, and consistent healthcare provisions to foster better psychosocial outcomes and pathways toward stability for street children.